Odpowiedź:
a) [tex](3+4)^{2} =7^{2} =49[/tex]
b) [tex]3^{2} +4^{2} =9+16=25[/tex]
c) [tex]4^{2} - (-3)^{3} -10^{3} *0,1=16-(-27)-1000*0,1= 16+27-100=-57[/tex]
d) [tex]\frac{1}{4}^{2} + 2^{3}* (-\frac{1}{2})^{3}= \frac{1}{4} +8*(-\frac{1}{8})=-\frac{3}{4} \\[/tex]
e) [tex](\frac{2}{3})^{2} *\frac{3^{2} }{4} - (-\frac{1}{2})^{2}=\frac{4}{9} *\frac{9}{4} -\frac{1}{4} = \frac{3}{4}[/tex]
f) [tex]\frac{2^{3}}{5} +\frac{2}{5^{3} } +(\frac{2}{5}) ^{3}= \frac{8}{5} +\frac{2}{125} +\frac{8}{125} =\frac{200}{125} +\frac{2}{125} +\frac{8}{125} = \frac{210}{125} =\frac{42}{25}=1\frac{17}{25}[/tex]
Szczegółowe wyjaśnienie: